A Mouse Model of Deep Vein Thrombosis Stability: The Effect of Direct Thrombin Inhibition - Saldanha, Lisa J. (My University, 2012)
The effect of direction thrombin inhibition on acute deep vein thrombosis (DVT) stability has not been defined and could contribute to pulmonary embolism (PE) risk. Direct thrombin inhibitors (DTIs) effectively inhibit free and clot-bound thrombin, which could potentiate thrombus instability through disruption of platelet, fibrin, and FXIIIa stabilizing mechanisms. This could manifest as increased thrombus embolization. A clinically relevant mouse model of DVT stability could further our understanding of venous thrombosis pathophysiology and define the effect of direct thrombin inhibition on PE. We hypothesized that acute DTI administration would decrease acute DVT stability and potentially increase PE risk. Platelets were labeled in vivo, femoral vein thrombosis was induced using FeCl3, and lepirudin (8U/g) was administered after clot formation. Using intravital videomicroscopy (IVM), real time embolization was quantified as a measurement of thrombus stability. Thrombus stability increased in the control group and decreased in the lepirudin-treated group over two hours. The decrease in α2-antiplasmin (α2-AP) content within lepirudin-treated thrombi, compared to control thrombi, could possibly contribute to the observed decrease in thrombus stability. Continued growth and embolization established the dynamic nature of formed thrombi. In both groups, emboli were detected in the pulmonary artery circulation. Therefore, we successfully developed a mouse model of venous thrombus stability, which imitated the clinical progression of DVT to PE. DTI administration in the acute DVT setting could decrease thrombus stability, demonstrated through increased embolization and PE. This model could be useful in examining the effect of other antithrombotics and risk factors settings on DVT stability.
Keywords: Deep vein thrombosis; pulmonary embolism; thrombus stability; anticoagulants; intravital microscopy; Hematology; Hematology